The Correlation between Task Commitment and Students’ EFL Learning Achievement - Jihat Nurrahman; Hodairiyah; Fajar Budiyono (ELE Reviews: English Language Education Reviews, 2022)
This research aims to prove whether there is a correlation between task commitment and students’ EFL Learning achievement on reading comprehension of the second-semester students of the Indonesian Language and Literature Education Study Program. This study used eleven questionnaire items of task commitment and learning achievement tests on giving and responding opinions. The sample of this research was 30 out of 165 students. Based on the calculation results using rser correlation, the correlation value of this study was 0.129. The correlation value was very low (almost uncorrelated) according to the interpretation table of the r value. A conclusion can be drawn that the task commitment, as one of the students’ internal factors, did not affect the students’ learning achievement.